Modified superstructure fiber Bragg grating for a filter application - Hemed, Ayser; Fdhala, Mayyada M.; Khorsheed, Suha M. (Kuwait Journal of Science, 2021)
Performance of a modified superstructure fiber Bragg grating is carried out by; simulation using a Matlab and then by optisystem7. Results for these two simulations are compared with experimental investigation for three special FBGs in additional to standard one. These four FBGs have one, two, three and four regions. Laser reflectance and transmittance spectra and their corresponding number of peaks and their bandwidths are observed and analyzed in a constant temperature and strain. Results for this investigation indicates enhancement for the modified FBG to be an effective filter which can be employed for communication as well as sensing. Filtering the transmitted signal could be satisfied in a simple and more efficiency than traditional device.